Perbedaan Motivasi Belajar Ditinjau Dari Faktor Demografi Mahasiswa Yang Mengikuti Perkuliahan Daring Universitas Negeri Padang - Febriyan Sukra Alhamda; Yuninda Tria Ningsih (Journal on Education, 2023)
The Differences In Learning Motivation In View Of The Demographic Factors Of Student Taking Online Lectures In State University Of Padang. This study aims to find out the difference in Learning Motivation In View Of The Demographic Factors Of Student Taking Online Lectures In State University Of Padang.. Quantitative approaches of comparative types are the methods used in this research. This study's population consists of students enrolled at the State University of Padang. In this study, random sample techniques were used, and subjects obtained as many as 150 people.In this data collection, we used the motivation to learn and the socioeconomic scale. The data were analyzed using a factorial ANOVA technique. The results showed a level of significance of sig = 0.351 (sig 0.05), meaning that there are no differences in learning motivation in view of the demographic factors of students taking online lectures at the State University of Padang.